Polarity-item anything in L3 English: Where does transfer come from when the L1 is Catalan and the L2 is Spanish?. (October 2018) - Puig-Mayenco, Eloi; Marsden, Heather
This study explores the source of transfer in third language (L3) English by two distinct groups of Catalan–Spanish bilinguals, simultaneous bilinguals and late bilinguals. Our study addresses two research questions: (1) Does transfer come from the first language (L1), the second language (L2), or both? and (2) Does age of acquisition of the L2 affect how transfer occurs? We compare beginner and advanced English speakers from both L3 groups with beginner and advanced L1-Spanish L2-English speakers, and find that, on an acceptablity judgment task that investigates knowledge of the distribution of polarity item anything, the two L3 groups demonstrate a different response pattern from the L2 group. The results suggest that both L3 groups transfer from Catalan, and not from their L2, Spanish. Additionally, the cross-sectional nature of the study shows that negative transfer from the initial stages of acquisition is overcome to different extents by the L3 vs. the L2 groups. We conclude that the results show strong evidence against the L2 status factor (Bardel and Falk, 2007, 2012) and the cumulative enhancement (Flynn et al., 2004) models of L3 acquisition, while they can be accounted for by the typological primacy model (Rothman, 2010, 2011, 2015), although other models that predict L1 transfer in L3 acquisition are not ruled out. Further, our findings show no effect of age of acquisition of the L2 on L3 development.